A Mobile Sleep-Management Learning System for Improving Students' Sleeping Habits by Integrating a Self-Regulated Learning Strategy: Randomized Controlled Trial - Chu, Hui-Chun; Liu, Yi-Meng; Kuo, Fan-Ray (JMIR Publications, 2018)
BackgroundInsomnia can significantly affect students' learning performance. Researchers have indicated the importance and challenge of coping with insomnia using nondrug treatments, such as cognitive behavioral therapy (CBT) for insomnia. However, it is easy for the traditional CBT for insomnia to be interrupted owing to the overly lengthy period of sleep therapy. Self-regulated learning (SRL) strategies are known to be an effective approach for helping students improve their time management, as well as their ability to set learning goals and adopt learning strategies. ObjectiveThe objective of this study was to propose a mobile sleep-management learning system integrated with SRL strategies and CBT. MethodsA total of 18 undergraduate students from a university in northern Taiwan participated in the 2-week experiment of using this sleep-management system. ResultsThe experimental results showed that the proposed approach was useful and easy for students to use. In addition, the number of students with insomnia significantly decreased; that is, the proposed approach could help students improve their sleep quality and cultivate better sleeping habits, which is important for them to enhance their learning efficiency. ConclusionsWith the assistance of this proposed approach, students can plan their daily life by setting goals, applying strategies, monitoring their life habits process, and modifying strategies to cultivate good learning and healthy lifestyle habits. Trial RegistrationGovernment Research Bulletin MOST104-3011-E038-001; https://www.grb.gov.tw/search/planDetail? id=11568383&docId=467988 (Archived by WebCite at http://www.webcitation.org/73MnPHNri)